A comparative study of low doses of intrathecal ketamine and midazolam with bupivacaine for postoperative analgesia in infraumbilical surgeries - M., Rajabhushanam; K., Sunil Kumar; Aasim, Syed Ali; S., Venkatesh (International Journal of Advances in Medicine, 2019)
Background: Infra-umbilical surgeries may be performed under local, regional (spinal or epidural) or general anaesthesia, spinal block is still a first choice, because of its rapid onset, high quality of blockade, lack of catheter related infection, less failure rate and also cost effective but the duration of block and postoperative analgesia is limited. The purpose of study was to compare the efficacy of adding ketamine to 0.5% hyperbaric bupivacaine with midazolam to 0.5% hyperbaric bupivacaine in elective infraumbilical procedures. Methods: A randomized, single blinded, clinical study. 60 subjects were enrolled from the patients presenting for elective infraumbilical surgeries after following the inclusion and exclusion criteria laid down for the study. Sixty ASA Grade I and II patients undergoing infra umbilical surgeries were randomly divided into one of the two equal groups (n=30). Results: Total 60 patients were included in this study. The mean time to achieve T10 sensory level and modified bromage scale III was prolonged in group M (4.33±1.09, 6.66±1.26 min) as compared to group K (3.3±0.7, 4.96±1.21 min) which was statistically significant (P value <0.05). Conclusions: The present study concludes that addition of intrathecal midazolam to hyperbaric bupivacaine provide very good and prolonged post-operative analgesia without significant intra-operative and post-operative side effects compared to intrathecal ketamine.